An Analytical Study of Translation Methods in the Song Rewrite the Stars by James Arthur and Anne-Marie: A Theoretical Application of Peter Newmark’s Framework - Syahrun Gunawan (CV. Tirta Pustaka Press, 2025)
This study aims to analyze the translation methods employed in the Indonesian rendering of the song “Rewrite the Stars” by James Arthur and Anne-Marie, using Peter Newmark’s (1988) classification of translation methods. Adopting a qualitative descriptive approach, the data were drawn from the original English lyrics and their Indonesian translation. Each line of the lyrics was examined to identify the translation method applied, including literal, faithful, semantic, communicative, and idiomatic translation. The findings reveal that communicative translation is the most dominant method (42%), followed by literal translation (26%), faithful translation (14%), semantic translation (12%), and idiomatic translation (6%). No instances of word-for-word, adaptation, or free translation were identified. These results suggest that the translator favors a communicative approach that prioritizes naturalness and comprehensibility in the target language, rather than methods that are overly rigid or excessively liberal. This study underscores the importance of selecting appropriate translation methods in song translation to ensure that emotional nuances, aesthetic qualities, and cultural elements are effectively conveyed to the target audience.